Fighting against COVID-19 requires wearing a face mask by not some but all - Hakan Yilmazkuday (Transportation Research Interdisciplinary Perspectives)
This paper investigates the effects of wearing a face mask on fighting against the coronavirus disease 2019 (COVID-19). The formal analysis is achieved by using a difference-in-difference design, where U.S. county-level data on changes in COVID-19 cases or deaths are regressed on lagged changes in social interaction of people measured by Google mobility. The main contribution is achieved by distinguishing between the effects of social interaction on COVID-19 in different U.S. counties based on the corresponding share of people wearing a face mask determined by Dynata surveys. After controlling for county-specific and time-specific factors, the results show that social interaction increases both COVID-19 cases and deaths across U.S. counties, unless more than (or equal to ) 85% of people in a county “always” wear a face mask. It is implied that people can have social interactions without any statistically significant effects on the spread of COVID-19, if a community-wide wearing of face masks can be achieved.